CoCrMo-base Alloys for Dental Applications Obtained by Selective laser melting (SLM) and CAD/CAM Milling - Santos,Claudinei dos (2020)
Abstract In this work, CoCrMo-base alloys specimens were produced by additive manufacturing using selective laser melting (SLM) as well as CAD/CAM milling. For SLM specimens, spherical particles were laser processed at 1320°C under argon atmosphere and submitted to thermal stress relieving at 750°C–45min. Specimens from CoCrMo blocks were milled by CAD/CAM machining and sintered at 1300°C–60min. The materials from both techniques were characterized by relative density, dilatometry, SEM/BSE, OM and XRD analysis. The mechanical properties were determined by Vickers hardness and tensile tests. The specimens from both techniques exhibited single phase γCo (FCC) and CTE of 14 x10-6 °C-1. Relative density of 95.4%/ 85.6%, hardness values near 400HV/ 350HV and UTS of 905MPa/ 780MPa were measured for SLM and CAD/CAM specimens, respectively. Higher relative density is the main factor for increased mechanical properties of SLM specimens. On the other hand, both SLM and CAD/CAM specimens present properties in accordance with ISO-22674 recommendations, compatible with dental applications such as bridges containing four or more elements as well as fully dense pontics.